A bold proposition: a participatory parity approach to radical flexibility in designing a postgraduate diploma - Gachago, Daniela; Govender, Shanali; Mayisela, Tabisa; Huang, Cheng-Wen; Hamman, Nadine; Cox, Glenda (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
This article explores the implementation of radical flexibility and social justice principles in the Blended and Online Learning Design (BOLD) programme at the University of Cape Town. Drawing on Fraser's concept of participatory parity and Veletsianos and Houlden's concept of radical flexibility, we explore how programme and course design can challenge traditional educational structures to create more equitable learning opportunities. The BOLD programme reimagines access to and success in postgraduate education by designing in response to Fraser's economic, cultural, and political dimensions. The programme responds to the maldistribution of resources by creating opportunities for flexible financial commitments and centring the use of open educational resources. BOLD responds to misrecognition by foregrounding diverse representations of identity through “course buddies” and personalised learning pathways that allow for flexible pacing. Thirdly, the programme responds to matters of misrepresentation by leveraging policy changes, creating varied entry points, and intentionally designing opportunities for students to shape the programme. Implementing these changes required navigating institutional constraints and exploring the capacity of systems to change. While the programme team remains committed to radical flexibility, this article demonstrates the potential of an interim and principled pragmatic flexibility that centres student agency while working to enhance flexibility in existing systems. This design case study contributes to ongoing discussion about the purpose of higher education, questioning not just how to deliver education equitably, but what kind of educational future we want, and for whom.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 6, Volume 9
Keywords: Online learning design; Blended learning design; Radical flexibility; Social justice; Online learning; Education; Instructional systems -- Design; Computer-assisted instruction; Education higher, South Africa; Graduate students -- South Africa